Twenty years experience with pit and fissure sealants - Sundfeld, Renato Herman [UNESP]; Briso, André Luiz Fraga [UNESP]; Mauro, Silvio José [UNESP]; De Alexandre, Rodrigo Sversut [UNESP]; Neto, Daniel Sundfeld; De Oliveira, Fernanda Garcia [UNESP]; Machado, Lucas Silveira [UNESP] (My University, 2009)
Twenty years of investigations on the use of pit and fissure sealants are presented with emphasis on application techniques, types of materials and long-term follow-up. After two decades of routine provision of pit and fissure sealants, we are able to conclude that placement of bonded resin sealant material is a highly effective approach for prevention of pit and fissure caries, provided the sealant material is correctly applied. © 2009 Nova Science Publishers, Inc.
Keywords: Application techniques; Pit and fissure sealant; Time analysis